Leptosphaeria maculans Effector Protein AvrLm1 Modulates Plant Immunity by Enhancing MAP Kinase 9 Phosphorylation - Ma, Lisong (iScience, 2018)
Leptosphaeria maculans, the causal agent of blackleg disease in canola (Brassica napus), secretes an array of effectors into the host to overcome host defense. Here we present evidence that the L. maculans effector protein AvrLm1 functions as a virulence factor by interacting with the B. napus mitogen-activated protein (MAP) kinase 9 (BnMPK9), resulting in increased accumulation and enhanced phosphorylation of the host protein. Transient expression of BnMPK9 in Nicotiana benthamiana induces cell death, and this phenotype is enhanced in the presence of AvrLm1, suggesting that induction of cell death due to enhanced accumulation and phosphorylation of BnMPK9 by AvrLm1 supports the initiation of necrotrophic phase of L. maculans infection. Stable expression of BnMPK9 in B. napus perturbs hormone signaling, notably salicylic acid response genes, to facilitate L. maculans infection. Our findings provide evidence that a MAP kinase is directly targeted by a fungal effector to modulate plant immunity.